2018
DOI: 10.1016/j.physletb.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

On the two-loop divergences of the 2-point hypermultiplet supergraphs for 6D, N=(1,1) SYM theory

Abstract: We consider 6D, N = (1, 1) supersymmetric Yang-Mills theory formulated in N = (1, 0) harmonic superspace and analyze the structure of the two-loop divergences in the hypermultiplet sector. Using the N = (1, 0) superfield background field method we study the two-point supergraphs with the hypermultiplet legs and prove that their total contribution to the divergent part of effective action vanishes off shell.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The explicit quantum harmonic superfield calculations confirming this statement were performed in[36,37].…”
mentioning
confidence: 73%
“…The explicit quantum harmonic superfield calculations confirming this statement were performed in[36,37].…”
mentioning
confidence: 73%
“…The main advantage of such a formulation is the possibility to keep manifest N = (1, 0) supersymmetry at all steps of quantum calculations. In our recent papers [44][45][46][47][48][49][50] we developed the harmonic superfield approach for calculating the lowest off-shell quantum corrections in various 6D, N = (1, 0) and N = (1, 1) supersymmetric theories. In the present paper we apply this superfield technique for studying the one-loop effective action in 6D, N = (1, 0) higher-derivative gauge theory of ref.…”
Section: Jhep08(2020)169mentioning
confidence: 99%
“…Although 6D, N = (1, 1) non-abelian SYM theory is non-renormalizable by power counting, it was proved that it is on-shell finite at one and two loops [28][29][30][31][32][33][34][35]. Moreover, it was recently shown that this theory is one-loop finite even off-shell [36][37][38] and that the two-loop diagrams with hypermultiplet legs are also off-shell finite [39].…”
Section: Jhep09(2018)039mentioning
confidence: 99%